Sport in the Black Atlantic: Cricket, Canada and the Caribbean diaspora - Joseph, Janelle (Globalizing Sport Studies, 2017)
"This book outlines the ways sport helps to create transnational social fields that interconnect migrants dispersed across a region known as the Black Atlantic: Britain, North America and the Caribbean. Many Caribbean men's stories about their experiences migrating to Canada, settling in Toronto's urban and suburban neighbourhoods, finding jobs, and travelling involved some contact with a cricket and social club. In this study Joseph brings a sport analysis to black diaspora research and shows how the cricket ground joins black Canadians as a unified community, to celebrate their homeland cultures and assuage the pain of racial terror that unifies the Black Atlantic. It offers a unique contribution to black diaspora studies through showing sport in Canada as a means of contending with ageing in the diaspora, creating transnational relationships, and marking ethnic boundaries on a local scale. The study also brings black diaspora analysis to sport research and takes a close look at what goes on before, during, and after cricket matches to provide insights into the dis-unities, contradictions and complexities of Afro-diasporic identity. The simultaneous representation of sameness and difference among Afro-Caribbean, African-American, Black British, Indo-Caribbean and South-Asian groups in Canada is played out on the cricket field. Sport in the Black Atlantic describes twenty-one months of ethnographic empirical evidence of how black identities are gendered, age-dependent and formed relationally, with boundary making and crossing as active processes in multicultural Canada. It will be of interest to students and scholars in sociology, sport studies, and black diaspora studies."